2017
DOI: 10.1111/jen.12390
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Orius insidiosus on alternative foods

Abstract: Orius insidiosus is economically important for biological control of pests of vegetable and ornamental crops. To improve pest control with this predator, its densities in the crops can be enhanced by the provision of alternative foods, especially when prey are scarce. We therefore compared the performance of O. insidiosus on three alternative foods (Ricinus sp. pollen, bee pollen and the mixed stages of the astigmatid prey Tyrophagus putrescentiae) that are cheaper than frozen eggs of Ephestia kuehniella. Juve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 43 publications
0
18
1
3
Order By: Relevance
“…Consumption of Thrips nymphs, T. absoluta, and H. armigera eggs by O. insidiosus was higher than those reported in the study by Coll & Ridgeway (1995), probably because we only offered only prey and no other supplementary sources of food, such as pollen or nectar (Bernardo et al 2017). We also found that C. sanguinea fed on more M. persicae than Tetranychus spp., probably because this predator commonly preys on the former species under field conditions (Oliveira et al 2005).…”
contrasting
confidence: 65%
“…Consumption of Thrips nymphs, T. absoluta, and H. armigera eggs by O. insidiosus was higher than those reported in the study by Coll & Ridgeway (1995), probably because we only offered only prey and no other supplementary sources of food, such as pollen or nectar (Bernardo et al 2017). We also found that C. sanguinea fed on more M. persicae than Tetranychus spp., probably because this predator commonly preys on the former species under field conditions (Oliveira et al 2005).…”
contrasting
confidence: 65%
“…These results are consistent with studies conducted with M. pygmaeus for which a diet of Ephestia eggs increased the total number of predators on tomato crops relative to control predator population growth 22 as well as for O . insidiosus for which this diet resulted in a greater oviposition rate relative to a diet of pollen or no food at all 29 . Eggs of E .…”
Section: Discussionmentioning
confidence: 95%
“…For anthocorid and mirid predators, food supplementation with plant or alternate prey resources can greatly improve their long-term crop establishment and contribute to a more sustainable pest management strategy 10,2225 . Traditionally, eggs of the Mediterranean flour moth, Ephestia kuehniella have been widely used as a food source to maintain populations of predatory bugs 2629 . However, due to the technical challenge of producing this food source 20 , its cost is generally considered prohibitive for wide scale application in crop food supplementation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Orius naivashae (Poppius); Orius thripoborus (Hesse) Bernardo et al, 2017;Bonte et al, 2017 Astigmatids: Aleuroglyphus ovatus (Troupeau); Austroglycyphagus lukoschusi (Fain); Blomia tropicalis; Carpoglyphus lactis L.; Suidasia medanensis (Oudemans); Thyreophagus cracentiseta Barbosa with purpose built automatized blowers. Supplying predatory mites with factitious (astigmatid) prey mites as food has recently gained popularity among growers.…”
Section: Anthocoridsmentioning
confidence: 99%